Stability of HIV-1 Nucleic Acids in Dried Blood Spot Samples for HIV-1 Drug Resistance Genotyping - Aitken, Susan C.; Wallis, Carole L.; Stevens, Wendy; de Wit, Tobias Rinke; Schuurman, Rob (PLOS ONE, 2015)
Dried blood spots (DBS) are an easy to collect sample-type that can stabilize biological material at ambient temperature for transport and storage, making them ideal for use in resource-limited settings (RLS). We investigated the effect of storage temperature and duration on ability to detect mixed HIV-1 viral RNA populations, and subsequently viral RNA populations in a background of proviral DNA. Part one of the study used DBS samples of whole blood spiked with specific quantities of HIV-1 subtype-B and -C RNA to study mixed virus population detection. Part two used DBS comprising of HIV-1 subtype-B proviral DNA containing U1 cells combined with HIV-1 subtype-C RNA to mimic HIV-1 infected clinical samples as a model system to study the relative stability of HIV-1 RNA and DNA in DBS. Prepared DBS were stored at -20°C and +30°C for periods of one day, one, two, and four weeks. Samples were genotyped to determine changes in the detection of mixtures in the sample over time. From two weeks onwards, storage at +30°C resulted in gradual, time-related reduction in the detection of mixed virus population at log10 VL 4.0 but not at log10 5.0. Proviral DNA and viral RNA were both stable for at least 52 weeks when stored at -20°C, compared to progressive RNA decay over time at +30°C. DBS storage conditions and duration had a significant effect on HIV-1 RNA amplification. Our results demonstrate that DBS storage at ambient temperature (+30°C) should not exceed two weeks, with long-term storage at -20°C or lower.